2003
DOI: 10.1093/brain/awg017
|View full text |Cite
|
Sign up to set email alerts
|

The non-classical MHC molecule HLA-G protects human muscle cells from immune-mediated lysis: implications for myoblast transplantation and gene therapy

Abstract: HLA-G is a non-classical MHC class I molecule with highly limited tissue distribution which has been attributed chiefly immune-regulatory functions. We previously have reported that HLA-G is expressed in inflamed muscle in vivo and by cultured myoblasts in vitro. Here, we used the in vitro models of human myoblasts or TE671 muscle rhabdomyosarcoma cells to characterize the functional role of HLA-G for muscle immune cell interactions. Gene transfer of the two major isoforms of HLA-G (transmembranous HLA-G1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 45 publications
5
58
1
1
Order By: Relevance
“…Exposure to TNF-␣ alone did not show any statistically significant effect on both MHC class I and MHC class II surface levels, although we noticed that expression levels of HLA-A, -B, and -C molecules were slightly higher upon TNF-␣. In line with previous data, TNF-␣ also showed a synergistic effect with IFN-␥ on MHC class I expression (8). IFN-␥ strongly induced both MHC class I and MHC class II expression.…”
Section: Tnf-␣ Regulates Mhc Expression In Ifn-␥-treated Primary Myocsupporting
confidence: 92%
See 1 more Smart Citation
“…Exposure to TNF-␣ alone did not show any statistically significant effect on both MHC class I and MHC class II surface levels, although we noticed that expression levels of HLA-A, -B, and -C molecules were slightly higher upon TNF-␣. In line with previous data, TNF-␣ also showed a synergistic effect with IFN-␥ on MHC class I expression (8). IFN-␥ strongly induced both MHC class I and MHC class II expression.…”
Section: Tnf-␣ Regulates Mhc Expression In Ifn-␥-treated Primary Myocsupporting
confidence: 92%
“…Skeletal myocytes are facultative antigen-presenting cells, and they actively participate in local immune reactions (5,6), which develop spontaneously during the course of autoimmune and infectious muscle diseases (7) or can be induced by immunotherapeutic gene transfer into muscle (8). Up-regulation of macroautophagy and lysosomal genes has been documented at the transcript and protein level in different settings in myopathies associated with immune cell infiltration (9 -13).…”
mentioning
confidence: 99%
“…Our findings dispute those of Fournel et al (14), who reported that partially purified sG stimulated Fas/FasL-mediated apoptosis in PHA-stimulated CTL function, but are in accord with those of Wiendl et al (46) and Le Friec et al (47), who also failed to identify death of HLA-G-treated cells. Possibly, different conditions of testing are the reason for the disparate results, or perhaps the preparations used in the earlier report (14) contained apoptosisinducing contaminants.…”
Section: Discussioncontrasting
confidence: 76%
“…HLA-G1 has a structure similar to that of classical HLA class I molecules: a heavy chain noncovalently associated with ␤-2 microglobulin and a nonameric peptide. Functional assays have demonstrated that HLA-G was able to inhibit allogeneic proliferation of T cells (2)(3)(4)(5), and natural killer cell cytotoxicity (6)(7)(8)(9)(10), as well as antigen-specific T cell cytotoxicity (5,11). HLA-G exerts its direct immunoinhibitory function through three inhibitory receptors, ILT2͞CD85j, ILT4͞CD85d, and KIR2DL4͞CD158d (12)(13)(14).…”
mentioning
confidence: 99%
“…Under pathological conditions, HLA-G is expressed (i) by allografts (15)(16)(17) and by infiltrating monocuclear cells within the transplanted tissues (17), (ii) during inflammatory diseases and by lesion-infiltrating HLA-G ϩ antigen-presenting cells (APCs) (5,18,19), (iii) by tumor tissues (20)(21)(22)(23)(24) and by tumor-infiltrating APC (24,25), and (iv) on monocytes and T cells from HIV patients (26).…”
mentioning
confidence: 99%